Unveiling CYP450 inhibition by the pesticide prothioconazole through integrated in vitro studies and PBPK modeling - Perovani, Icaro S.; Yamamoto, Priscila A.; da Silva, Rodrigo M.; Lopes, Norberto P.; de Moraes, Natalia V.; de Oliveira, Anderson R. M. [UNESP] (Springer Nature, 2025)
Prothioconazole (PTC), a widely used triazole fungicide with low human toxicity, was evaluated for its potential to inhibit human cytochrome P450 (CYP450) enzymes and its implications for pesticide-drug interactions (PDI). Through in vitro assays, PTC demonstrated significant inhibition of CYP2C9, CYP2C19, and CYP3A, with inhibition constant (Ki) values ranging from 0.08 to 5.88 µmol L⁻1. Initial predictions using a basic static model suggested potential for PDI, particularly with CYP2C9 substrates. To refine these predictions, a physiologically-based pharmacokinetic (PBPK) rat model was developed using mass balance studies and pharmacokinetic data across doses of 2 and 150 mg kg−1. The model's accuracy was confirmed by simulated versus observed maximum plasma concentration (Cmax) and area under the plasma concentration–time curve (AUC) values, with errors remaining within two-fold. The rat model was subsequently extrapolated to humans using in vitro binding and metabolism data. Simulations with 10 virtual trials, each involving 10 fasted human subjects, assessed PDI potential under multiple daily doses of PTC at multiples of the acceptable daily intake (ADI, 0.05 mg kg−1). AUC ratios for CYP3A (midazolam, nifedipine), CYP2C19 (omeprazole), and CYP2C9 (tolbutamide) substrates indicated no significant inhibition at ADI levels. This study underscores the safety of PTC in terms of PDIs at dietary exposure levels and highlights the utility of PBPK modeling as a robust tool for pesticide risk assessment. The findings strengthen confidence in PTC’s safety for human health.